The Gendered Relationship between Parental Religiousness and Children's Marriage Timing. (8th May 2020) - Brauner-Otto, Sarah R; Pearce, Lisa
Abstract: In this article, we examine whether mother's and father's self-reported religiousness relates differently to the timing of their children's marriages. Conceptualizing religion as one source of cultural schema about marriage that is likely to conflict with other schemas for living, and theorizing that women are more likely to experience structured ambivalence over religious schema and their enactment than men, we predict father's religiousness will be associated with children's marriage in accordance with religious dogma, whereas the experience of structured ambivalence yields a more complex relationship between mother's religiousness and their children's marriage. Using longitudinal data from the Chitwan Valley Family Study in Nepal, a primarily Hindu and Buddhist setting, we find contrasting associations between son's marriage timing and mothers' and fathers' religiousness. This provides empirical support for theoretical frameworks that emphasize the gendered nature of religious identity and suggests the influence of religion on other aspects of life is gendered.